(untitled) (IITM Journal of Business Studies, 2024)
Financial planning necessitates a comprehensive assessment of an individual's current and future financial circumstances. This study aims to review and assess the existing literature on retirement financial planning with 9397 research. While financial planning, in general, has received substantial attention, retirement specific planning remains fragmented and limited.The available literature is disjointed, predominantly subjective, and narrow in scope. Notably, despite a recent surge in research prompted by the pandemic, investment and financial planning remain underrepresented in conjunction with retirement and pension keywords. This study offers valuable insights for academics and policymakers to identify areas necessitating further research in retirement financial planning.